United States : Publication of Financial Sector Assessment Program Documentation; Reports on Observance and Codes. (IMF Staff Country Reports; Country Report ;, 2010)
The report gives a summary of the detailed assessment report on the implementation of the Basel Core Principles for Effective Banking in the United States and its recommendations, securities and futures market regulatory, insurance regulation, Fixed Income Clearing Corporation -Government Securities Division (FICC-GSD) system, and other recommendations such as Depository Trust Company (DTC) against the Recommendations for Securities Settlement Systems (RSSS), the National Securities Clearing Corporation (NSCC) against the Recommendation for Central Counterparties (RCCP), the Fedwire Securities Service (FSS) against the Committee on Payment and Settlement Systems -International Organization of Securities Commission (CPSS-IOSCO) RSSSs as well. The U.S. authorities welcomed the Financial Sector Assessment Program (FSAP) and independent reviews, and appreciated significant undertaking associated with reviews in the wake of the crisis.